Proceedings of the Mizoram Science Congress 2018 (MSC 2018) - Perspective and Trends in the Development of Science Education An 2018
DOI: 10.2991/msc-18.2018.32
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of radon content in water using SMART RnDuo in Mizoram, Northeast India

Abstract: Radon is a radioactive inert gas that is produced naturally from the decay of uranium to radium. As it is formed, it is released into air or water-containing pores between soil and rock particles. From soil and rock natural forces move it into the earth and it dissolves in groundwater. This is of great medical concern as environmental radon is one of the major causes of dangerous health problems such as lung cancer. Measurements of radon content in water was carried out in the northeastern part of India namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…The geothermal springs or hot-water springs are present in the states of West Bengal, Sikkim, Arunachal Pradesh, Assam, Meghalaya, Odisha, Bihar and Jharkhand, and in the Andaman and Nicobar Islands of the eastern part of India (https://geographyandyou.com/hot-water-spri ngs-in-india/) (21) . Various research studies determined the radioactivity levels in spring waters in different region of eastern part of India (24)(25)(26) . A study reported that the presence of helium in thermal springs of Odisha state is possibly due to disintegration of radioactive elements in Pre-cambrian terrain (27) .…”
Section: Reason For Selecting the Regions Of Eastern Part Of Indiamentioning
confidence: 99%
See 1 more Smart Citation
“…The geothermal springs or hot-water springs are present in the states of West Bengal, Sikkim, Arunachal Pradesh, Assam, Meghalaya, Odisha, Bihar and Jharkhand, and in the Andaman and Nicobar Islands of the eastern part of India (https://geographyandyou.com/hot-water-spri ngs-in-india/) (21) . Various research studies determined the radioactivity levels in spring waters in different region of eastern part of India (24)(25)(26) . A study reported that the presence of helium in thermal springs of Odisha state is possibly due to disintegration of radioactive elements in Pre-cambrian terrain (27) .…”
Section: Reason For Selecting the Regions Of Eastern Part Of Indiamentioning
confidence: 99%
“…Assessment of radon content in 64 water samples from different water sources in two districts of Aizawl and Kolasib of the state of Mizoram has been conducted in a study (25) . The water samples examined in this study have been collected from stream https://www.indjst.org/ water, spring water, pump water, open well, pond and from government supplied water.…”
Section: Mizorammentioning
confidence: 99%